Pengaruh Norma Subjektif, Pengetahuan Laporan Keuangan, dan Literasi Finansial terhadap Minat Investasi pada Mahasiswa - Ichsan Susanto; Atik Djajanti (Sekolah Pascasarjana Perbanas Jakarta, 2021)
This research aim to examine the effect of subjective norm, financial statement knowledge and financial literacy to students’ investing interest. Observations are done for 98 post graduate students in major of economy in Jakarta. This research is a quantitative research and using Structural Equation Modelling (SEM) for the research method. The result found out that subjective norm, financial statement knowledge, and financial literacy have a positive effect to students’ investing interest.